The use of Poster as a Medium for Introducing Children’s English Vocabulary in St. Paul Kindergarten Maumere - Henderikus Dasrimin; Didimus D. K. Moan Wodo (Jurnal Pendidikan Vokasi Indonesia, 2025)
Supporting learning resources plays an essential part in enhancing students' English proficiency levels. Consequently, introducing English vocabulary to children at a young age, such as in kindergarten, is essential, and it is the teacher's duty to incorporate learning media during the teaching process. This study aims to explore kindergarten teachers’ perceptions and experiences regarding the use of posters as teaching tools. This research utilized a qualitative descriptive methodology. Data were gathered through observation of 20 students (5-6 years old) in the classroom during their learning activities and through semi-structured interviews with the principal and teacher of St. Paul Kindergarten Maumere. In examining the data, we analyzed interview transcripts by reviewing the interview outcomes to comprehend the data. The findings indicated that posters may serve as a tool to teach English vocabulary to kindergarteners. Moreover, it aids them in understanding and retaining English vocabulary. Interestingly, they were excited about learning English through posters.